2015
DOI: 10.1155/2015/243527
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Neck Mass: A Case of a Parathyroid Cyst and Review of the Literature

Abstract: Parathyroid cysts (PC) are an unusual cause of neck swellings. The majority are nonfunctioning and prove to be a diagnostic challenge given their nonspecific physical and radiological characteristics. This is compounded by their rare occurrence, leading them to be overlooked in the differential diagnosis of neck lumps. Imaging techniques fail to determine the origin of these lesions, but a preoperative diagnosis can be achieved by fine-needle aspiration and measurement of cystic fluid C-terminal parathyroid ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…[1,3,7] Although most of these theories are associated with embryologic remnants, there are no pediatric cases reported in the literature. [7] The differential diagnosis for PC include a variety of conditions such as thyroid pathologies (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[1,3,7] Although most of these theories are associated with embryologic remnants, there are no pediatric cases reported in the literature. [7] The differential diagnosis for PC include a variety of conditions such as thyroid pathologies (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…[1,3,7,9] It has been reported that ultrasound, computerized tomography or magnetic resonance imaging may be helpful in discriminating solid/cystic cervical masses and showing their anatomical relation, and that thyroid scintigraphy may be helpful in revealing the presence of non-functional cysts, however none of these imaging methods can discriminate the thyroid/parathyroid origin of the lesions. [1,3,[7][8][9] In physical examination, PCs are soft, mobile masses. They have a semitransparent thin wall with smooth and shiny surface, that can easily be dissected from the thyroid tissue and surrounding tissues.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The symptoms of nonfunctioning cysts are limited to those caused by compression of neighbouring structures whereas the problems associated with functioning cysts are related to excessive secretion of PTH and subsequent hyperparathyroidism and hypercalcaemia (45)(46)(47).…”
Section: © C I C E D I Z I O N I I N T E R N a Z I O N A L Imentioning
confidence: 99%